2018
DOI: 10.1212/wnl.0000000000006355
|View full text |Cite
|
Sign up to set email alerts
|

MRI load of cerebral microvascular lesions and neurodegeneration, cognitive decline, and dementia

Abstract: ObjectiveTo explore the differential associations of neurodegeneration and microvascular lesion load with cognitive decline and dementia in older people and the modifying effect of the APOE genotype on these associations.MethodsA sample of 436 participants (age ≥ 60 years) was derived from the population-based Swedish National study on Aging and Care in Kungsholmen, Stockholm, and clinically examined at baseline (2001–2003) and 3 occasions during the 9-year follow-up. At baseline, we assessed microvascular les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 39 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…However, previous studies have shown that not only the presence or absence of lacunar infarcts 15 and WMH predicts dementia, but the number of lacunar infarcts and the severity of WMH have additional predictive value. 15,19 Therefore we constructed an amended score in which there were a number of categories for both the number of lacunar infarcts and the severity of WMH. This amended score appeared to improve the predictive ability slightly.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that not only the presence or absence of lacunar infarcts 15 and WMH predicts dementia, but the number of lacunar infarcts and the severity of WMH have additional predictive value. 15,19 Therefore we constructed an amended score in which there were a number of categories for both the number of lacunar infarcts and the severity of WMH. This amended score appeared to improve the predictive ability slightly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comparisons to our results in this regard could not be made. 49 In contrast, we used quantitative WMH volume as a continuous predictor and 3 cognitive domains as outcomes rather than global cognitive score in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the EPVS score in the region of basal ganglia significantly correlated to the severity of tremor and the EPVS score in the region of centrum semiovale was much higher in PD patients of PIGD motor phenotype than that in patients of the non PIGD motor phenotype. Currently, clinical studies have mainly focused on investigating the association between EPVS and cognitive impairment, poor blood pressure control or disease worsening in patients with dementia (Wang et al., ), stroke (Liu et al., ), or systematic inflammation (Cavallari et al., ). The relevant studies proposed that a higher EPVS severity degree might result in impaired cerebrovascular reactivity, blood‐brain barrier dysfunction and perivascular inflammation in the diseases (Brown et al., ).…”
Section: Discussionmentioning
confidence: 99%